Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1128/jvi.76.9.4241-4250.2002
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Neutralizing and Nonneutralizing Epitopes in the Porcine Reproductive and Respiratory Syndrome Virus GP5 Ectodomain

Abstract: After infection of swine with porcine reproductive and respiratory syndrome virus (PRRSV), there is a rapid rise of PRRSV-specific nonneutralizing antibodies (NNA), while neutralizing antibodies (NA) are detectable not sooner than 3 weeks later. To characterize neutralizing epitopes, we selected phages from a 12-mer phage display library using anti-PRRSV neutralizing monoclonal antibody (MAb) ISU25-C1. In addition, phages carrying peptides recognized by swine antibodies with high seroneutralizing titer were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
187
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(207 citation statements)
references
References 36 publications
5
187
0
Order By: Relevance
“…Gp5, especially in the ectodomain, possesses many N-glycosylation sites, and it has been shown that both neutralizing and nonneutralizing epitopes exist in this major structural protein with some of these functional sites already identified [41][42][43]. Our results showed that viral ORF5 of recent outbreaks in China had undergone accelerated evolution, and this result accorded with previous studies that evolution of PRRSV was driven by positive selection [25,44] .…”
Section: Resultssupporting
confidence: 94%
“…Gp5, especially in the ectodomain, possesses many N-glycosylation sites, and it has been shown that both neutralizing and nonneutralizing epitopes exist in this major structural protein with some of these functional sites already identified [41][42][43]. Our results showed that viral ORF5 of recent outbreaks in China had undergone accelerated evolution, and this result accorded with previous studies that evolution of PRRSV was driven by positive selection [25,44] .…”
Section: Resultssupporting
confidence: 94%
“…As expected, we found hotspots of nonsynonymous variation in the regions of the SIV ver envelope gene that correspond to the "highly variable loops" that are preferentially targeted by host antibodies (23,46). We found a similar pattern of adaptive changes in the DMVV-1 genome, with signatures of nonsynonymous diversity found primarily in genes that code for envelope glycoproteins and/or regions corresponding to antibody epitopes that have been extensively mapped in other arteriviruses (47)(48)(49)(50)(51). This observation suggests that vervet monkeys infected with DMVV-1 produce antibodies that target DMVV-1 glycoproteins but that these antibodies may not be effective in clearing DMVV-1 infection, a scenario that may be akin to immune escape observed during SIV infection.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, reverse genetics of an infectious cDNA clone was used to confirm that a single amino acid deletion at position 10 in M of KS62 resulted in escape from broadly neutralizing sera, 16-45 and 15-4, while retaining sensitivity to serum with homologous neutralizing activity. The results suggest that epitopes recognized by sera with different neutralization properties are distinct, which can explain the large number of neutralizing epitopes previously described in the literature (12)(13)(14)(15)(16)(17). The results also point to the importance of thoroughly characterizing the neutralization properties of polyclonal and monoclonal antibodies used for epitope mapping experiments.…”
mentioning
confidence: 54%
“…S1C in the supplemental material). Ostrowski et al (16) and Plagemann et al (17) described an epitope in GP5 in a type 2 genotype virus located in the vicinity of two conserved glycosylation sites in the ectodomain region (epitopes a and b in Fig. S1F in the supplemental material).…”
mentioning
confidence: 99%